2021
DOI: 10.1108/mhsi-08-2020-0050
|View full text |Cite
|
Sign up to set email alerts
|

Nurses burnout, resilience and its association with safety culture: a cross sectional study

Abstract: Purpose The purpose of this study was to assess burnout, resilience and the association with safety culture in nurses working in mental health institutions in Jazan government Hospital. Design/methodology/approach A cross-sectional survey using convenience sampling, with 119 nurses from the Jazan hospital between June and August 2018 was used. Findings The results of this study showed that 45.6% of the participants experienced a high level of emotional exhaustion, 36.5% reported a high level of depersonali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…trait‐like, capacity or process). Authors' referred to knowledge of resilience derived from several fields including psychology ( n = 5; Chang et al, 2019; Delgado et al, 2020; Delgado et al, 2021; Delgado et al, 2022; Foster et al, 2020), nursing ( n = 5; Dahan et al, 2022; Dogan & Boyacıoglu, 2021; Henshall et al, 2020;Majrabi et al, 2021; Xu et al, 2021), both nursing and psychology ( n = 4; Abram & Jacobowitz, 2021; Dehvan et al, 2018; Ramalisa et al, 2018; Xu et al, 2022) and mental health nursing (Sukut et al, 2022). One study acknowledged there is a lack of an agreed definition of resilience in mental health nursing (Delgado et al, 2020), and two others noted that the primary focus of resilience research in mental health nursing has been on individual resilience rather than inclusive of its complex and multidimensional nature (Dahan et al, 2022; Delgado et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…trait‐like, capacity or process). Authors' referred to knowledge of resilience derived from several fields including psychology ( n = 5; Chang et al, 2019; Delgado et al, 2020; Delgado et al, 2021; Delgado et al, 2022; Foster et al, 2020), nursing ( n = 5; Dahan et al, 2022; Dogan & Boyacıoglu, 2021; Henshall et al, 2020;Majrabi et al, 2021; Xu et al, 2021), both nursing and psychology ( n = 4; Abram & Jacobowitz, 2021; Dehvan et al, 2018; Ramalisa et al, 2018; Xu et al, 2022) and mental health nursing (Sukut et al, 2022). One study acknowledged there is a lack of an agreed definition of resilience in mental health nursing (Delgado et al, 2020), and two others noted that the primary focus of resilience research in mental health nursing has been on individual resilience rather than inclusive of its complex and multidimensional nature (Dahan et al, 2022; Delgado et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In eight studies, resilience was viewed as a personal quality, a capacity or an ability to cope (Dehvan et al, 2018; Henshall et al, 2020; Xu et al, 2022), to overcome challenges (Majrabi et al, 2021; Xu et al, 2021), to bounce back from adversity (Abram & Jacobowitz, 2021) or resist and thrive against adversities (Dogan & Boyacioglu, 2021; Ramalisa et al, 2018). Chang et al (2019) defined resilience as a ‘positive trait’ (p. 1) and stated ‘resilience was found to be a coping technique endorsed by mental health professionals’ to manage work‐related stress (p. 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the findings, 45.6% of nurses expressed increased emotional tiredness, 35.5% reported a high level of depersonalization, and only 15.9% reported a high level of personal success. The study found that the findings strongly suggested the prevalence of these burnout characteristics, which have a detrimental impact on nurses' and patients' safety and resilience and OHS [8].…”
Section: Impact Of Psychological Factorsmentioning
confidence: 83%